What Does Someone's Gender Identity Signal to Employers? - Hannah Van Borm; Marlot Dhoop; Allien Van Acker; Stijn Baert (Institute of Labor Economics (IZA), 2020)
Purpose - The purpose of this paper is to explore the mechanisms underlying hiring discrimination against transgender men. Design/methodology/approach - The authors conduct a scenario experiment with final-year business students in which fictitious hiring decisions are made about transgender or cisgender male job candidates. More importantly, these candidates are scored on statements related to theoretical reasons for hiring discrimination given in the literature. The resulting data are analysed using a bivariate analysis. Additionally, a multiple mediation model is run. Findings - Suggestive evidence is found for co-worker and customer taste-based discrimination, but not for employer taste-based discrimination. In addition, results show that transgender men are perceived as being in worse health, being more autonomous and assertive, and have a lower probability to go on parental leave, compared with cisgender men, revealing evidence for (positive and negative) statistical discrimination. Social implications - Targeted policy measures are needed given the substantial labour market discrimination against transgender individuals measured in former studies. However, to combat this discrimination effectively, one needs to understand its underlying mechanisms. This study provides the first comprehensive exploration of these mechanisms. Originality/value - This study innovates in being one of the first to explore the relative empirical importance of dominant (theoretical) explanations for hiring discrimination against transgender men. Thereby, the authors take the logical next step in the literature on labour market discrimination against transgender individuals.
Keywords: J15; J71; J16; J24; J23; 330; signalling; theories of discrimination; fictitious hiring decisions; transgender men; scenario experiment; risk aversion